PEEP titration guided by electrical impedance tomography in critically ill mechanically ventilated patients with acute hypoxemic respiratory failure - Dimitar Kazakov; Emral Kyosebekirov; Siyana Nikolova-Kamburova; Valentin Stoilov; Emil Mitkovski; Georgi Pavlov; Chavdar Stefanov; Milena Sandeva (Folia Medica)
Introduction: Positive end-expiratory pressure (PEEP) titration is crucial for improving oxygenation and preventing ventilator-induced lung injury in acute hypoxemic respiratory failure. Electrical impedance tomography (EIT) offers real-time, bedside monitoring of lung ventilation distribution, potentially guiding individualized PEEP settings. Aim: The aim of this study was to assess the effect of EIT-based PEEP titration on respiratory mechanics and gas exchange in critically ill mechanically ventilated patients with acute hypoxemic respiratory failure. Materials and methods: A prospective, interventional study was conducted from April 2022 to January 2024, including adult patients with acute hypoxemic respiratory failure on invasive mechanical ventilation. Continuous EIT monitoring was performed with electrode belts positioned at the fourth to fifth intercostal space. Patients were divided into two groups, low and high recruiters, based on the absolute reduction of the collapse percentage in the dorsal lung segments measured by EIT when increasing PEEP from 6 mbar to 20 mbar. EIT data, respiratory mechanics parameters and arterial blood gases were obtained during PEEP titration maneuvers. Optimum PEEP based on EIT was defined as the crossing point of the collapse and overdistention curves, generated during decremental PEEP trial. Results: A total of 45 patients with a mean age of 54.33 years were included in the study. In low recruiters, the EIT-based PEEP was lower (9.18±2.11) than baseline PEEP (10.73±3.07) (p=0.0008). In high recruiters, the EIT-based PEEP was higher (13.91±2.45) than baseline PEEP (10.22±2.24) (p=0.0006). A statistically significant positive correlation was found between BMI and EIT-based PEEP. The crossing point method of PEEP titration led to improvement of oxygenation in high recruiters and improvement of respiratory mechanics parameters in low recruiters. Conclusion: As a non-invasive and radiation-free monitoring tool EIT allows personalization of PEEP titration with minimum alveolar collapse and overdistention.